Chronic use of benzodiazepines among the elderly: losses and long-term harm (Research, Society and Development, 2023)
The chronic use of psychotropic drugs is increasingly present in the population. Benzodiazepines (BZD) are psychotropic drugs whose main clinical indications are related to anxiety, insomnia, panic syndromes, muscle relaxation, epilepsy and relief of spasticity resulting from central nervous system pathologies. The realization of this research is justified by its academic, scientific and social relevance, having in mind, to present the probability of dependence, damage, personal, social and physical effects caused by the chronic use of benzodiazepine psychotropics. Thus, the objective was to highlight the losses and long-term harm caused by the chronic use of benzodiazepines among the elderly. Methodology: This is an integrative literature review study, carried out through a data survey, through the scientific bases: LILACS, SCIELO and PUBMED. Results and Discussion: The literature presented clear answers about the main damage caused by the involuntary and chronic use of benzodiazepines. In elderly users, this condition is one of the most common psychiatric emergencies. Allied to this, in the prolonged use of benzodiazepines, cognitive deficits are considered a side effect that may appear in the medium and long term, causing impacts on the physical, emotional and social activities of the elderly. Complications arising from cognitive deficits vary according to changes in the level of consciousness. Conclusion: Side effects in the elderly are associated with cognitive decline, as it reduces exercise capacity and increases the risk of falls and fractures.